Use of Pulsed-Field Gel Electrophoresis to Determine the Source of Methicillin-Resistant Staphylococcus aureus Bacteremia - Eugene Y. H. Yeung; Ivan Gorn (MDPI AG, 2021)
Pulsed-field gel electrophoresis (PFGE) has historically been considered the gold standard in fingerprinting bacterial strains in epidemiological studies and outbreak investigations; little is known regarding its use in individual clinical cases. The current study detailed two clinical cases in which PFGE helped to determine the source of their methicillin-resistant Staphylococcus aureus (MRSA) bacteremia. Patient A was found to have MRSA bacteremia after trauma in her pelvic area. MRSA was also found in her groin but not in her nostril and rectum. PFGE was performed that showed variable bands of her MRSA isolates from blood and groin, suggestive of different strains of MRSA. Her MRSA bacteremia was determined to be unrelated to her pelvic trauma. Patient B was found to have MRSA bacteremia after colonoscopy. MRSA was also found in his nostril and rectum. PFGE was performed that showed variable bands of his MRSA isolates from blood and rectum but identical bands of MRSA isolates from his blood and nostril. His MRSA bacteremia was determined to be unrelated to his colonoscopy procedure. The current study demonstrates the use of PFGE to rule out the source of bacteremia in individual clinical cases.